Minimal genetically encoded tags for fluorescent protein labeling in living neurons - Aleksandra Arsić; Cathleen Hagemann; Nevena Stajković; Timm Schubert; Ivana Nikić-Spiegel (Nature Communications, 2022)
Site-specific labelling of proteins can be performed with unnatural amino acids combined with bioorthogonal click chemistry. Here the authors establish this in living neurons, using neurofilament light chain; they show combination with CRISPR/Cas9 engineering to tag the endogenous protein.